The nexus between worldwide governance indicators and hydropower sustainable growth in EU 28 region - Abdul Samad @ Iammi, Abdul Rahim; Alsaleh, Mohammed (University of Tehran, 2021)
This investigation intends to answer the question of whether worldwide governance indicators have an impact on the improvement of the hydropower industry in 28 European Union (EU) countries from 1996 until 2018. Applying the panel fully modified ordinary least squares (FMOLS), the outcomes demonstrate the inclined hydropower industry growth and an increase in worldwide governance indicators. While opinions and responsibilities, governmental steadiness, effective governance, judicial enforcement, quality administration, and control of fraudulent conduct were found to expand the hydropower industry growth. The results illustrate that hydropower industry growth in EU28 states is well increased by improving the quality of worldwide governance indicators in production and operation procedures. Ultimately, it will help in the global warming discussions. The evaluated outcomes are believed to be justifiably validated by panel dynamic ordinary least squares (DOLS) and pooled ordinary least squares (OLS). The paper endorsed in the EU28 region to expand the role hydropower industry in worldwide governance to achieve hydropower growth and lessen CO2 releases. The authorities in the EU28 region should have more financial aid in hydropower governance to improve its hydroelectricity production and availability. The EU28 region administrations can focus on the efficacy of hydropower governance to attain hydroelectricity guarantee, sustainability, and to lessen traditional oil dependency, correspondingly.